Developing Language Skills in Preschool Children through Games (European Journal of Language and Literature, 2018)
Preschool institution as a first level of the unified system of education bases its activity on the “student centered” philosophy of education which promotes different ideas from that of traditional education. Through organized activities in all its field activities foreseen in a curricula, the preschool institution with its structured environment in harmony with the goals and concrete objectives offers numerous possibilities to develop general abilities of children, which create appropriate conditions to prepare and offer optimal readiness to master the reading and writing skills. The activities that we handle and which aim accomplishment of this concrete objective come out and are supported by the living context of children in accordance to fulfillment and urging of the knowing interests for developing and deepening the knowledge of letters, sounds, reading and writing. In this view, children should not be imposed or prevent the interest they show in order to learn letters, sounds, reading and writing. Working with children of this age in order to understand and learn letters isn’t a program-based obligation because this is the school’s duty and not the preschool institution’s obligation. Obligations cause unwanted consequences which generate different psych-neurotic disorders. Overwork and heavy workload of these children, diminishes or misplaces children’s trust on possibilities of overcoming difficulties in learning basic letters, sounds, reading and writing. In addition, it diminishes and misplaces their interest in continuing school and the learning process. Therefore in order to prevent these negative consequences, there is an immediate need for a general preparation which offers children a possibility to transfer and generate skills in specific fields and content. The best strategy to prepare children to recognize letters, sounds and master reading and writing is no doubt activity through games which in this case represents the main substance for organizing activities in aspects of integrated education within preschool institutions.